Determination of microplastic in various freshwater fish species from agriculture fishpond in Tanjong Karang, Selangor - Zarawi, Nur Amany Husna (2023)
Microplastic (MP) contamination in fish species is one of the emerging environmental issues due to the increase in plastic pollution in the environment. As a result, this research looked into the abundance, properties, and variation of MPs in various commercial freshwater fish species from Tanjong Karang. Twelve fish from diverse feeding zones were taken to determine the variation in MPs ingestion rate between feeding zones. MPs were discovered in the gastrointestinal tracts (GIT) of 29.25% of all fish samples studied, which is greater than previously reported findings in other regions. Anabas testudineus has the highest concentration of MPs of any fish species. Microscopic examinations (Optical microscope Leica DM2500) revealed that MPs were dominated the film of morphotype and white colour. FTIR research revealed that the polymers discovered in fish GIT were high density polyethene and polypropylene. The results of this study demonstrate that demersal fishes had a higher concentration of MPs than benthopelagic and pelagic fishes, indicating that plastic ingestion in fish may be related to the feeding habitat. Our findings will assist people to understand which freshwater fishes and fishes from which feeding zones in Tanjong Karang are more contaminated with MPs for human consumption.